Exploring Local Wisdom: a Qualitative Study of Innovation in Traditional MSMEs in the Digital Era - Asrianto Asrianto; Anwar Ramli; Amiruddin Tawe; Anwar Rauf; Romansyah Sahabuddin; Masnawaty Sangkala; Samirah Dunakhir (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
This research aims to explore the forms, meanings, and processes of innovation undertaken by traditional Micro, Small, and Medium Enterprises (MSMEs) in facing the challenges of the digital era, with a particular emphasis on the role of local wisdom as a foundation for innovation. Using a qualitative approach with a case study design, this research explores the subjective experiences of MSMEs integrating cultural values with technological transformation. Data collection was conducted through in-depth interviews, participant observation, and document analysis, which were then analyzed using thematic methods. The results show that innovation in traditional MSMEs is not solely focused on technological aspects, but rather is the result of negotiations between cultural values, social adaptation, and modern market demands. Local wisdom has proven to be a source of values and ethics in product development, marketing strategies, and the digital transformation process. The innovation process occurs contextually and gradually, and is heavily influenced by community support and strong local social networks. This study confirms that culture-based innovation strategies provide a more sustainable and inclusive direction for MSMEs navigating the digital era. Therefore, digital transformation should not be separated from the social and cultural context in which MSMEs are rooted. This approach opens up space for a new understanding of more holistic innovation, which is not only technology-oriented, but also strengthens local identity and social cohesion within the MSME ecosystem.